Feed Utilization Strategies for Improved Ruminant Production in the Arid Region - Nashlai, I V; Bonsi, M L.K; Umunna, N N; Sileshi, Z; Bediye, S (Annals of Arid Zone, 2016)
This review scans through the attributes of feed resources prevalent in the arid and semi-arid zones ( ASAZ). The merits of the various biological and chemical attributes of feeds are discussed with a view to suggest those that could yield suitable and reliable indices for selecting potential feedstuff's among forage legumes. The review contends that besides protein Content. the rate of degradation and bulk density are two other legume factors that determine the extent of substitution of the basal roughage diet which will vary in direct proportion with roughage quality. The appropriate combinations of roughage and supplements have been advocated for sustainable livestock production in the ASAZ. Whilst most legumes contain more protein than is required to balance the fermentable energy in them and thus are suitable as supplements, their ability to supply both rumen degradable protein and escape protein is varied. The review argues that the slow uptake of supplementation strategies among others is due to unsurmountable logistics which can be eased by creating feed or protein banks. In relation to issues on feed availability the authors suggest that the use of feed resource on a regional scale could be maximized by (1 ) integrating weather information and satellite images to forecast feed distribution. patterns and (2) encouraging the establishment of communal silage pits. Pertinent researchable issues were highlighted.